2021
DOI: 10.35940/ijisme.b1280.037221
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition using Support Vector Machines as a Solution for Non-Technical Losses in Electricity Distribution Industry

Abstract: Contending with Non-Technical Losses (NTL) is a major problem for electricity utility companies. Hence providing a lasting solution to this menace motivates this and many more research work in the electricity sector in recent times. Non-technical losses are classed under losses incurred by the electricity utility companies in terms of energy used but not billed due to activities of users or malfunction of metering equipment. This paper therefore is aimed at proffering a solution to this problem by first detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…By utilizing the ensemble bagged tree (EBT) method, Aniedu et al [17] proposed a novel strategy for NTL identification in PDCs. Results showed that the EBT algorithm had a 93.1% accuracy rate for detecting NTLs, which was significantly greater than that of more traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing the ensemble bagged tree (EBT) method, Aniedu et al [17] proposed a novel strategy for NTL identification in PDCs. Results showed that the EBT algorithm had a 93.1% accuracy rate for detecting NTLs, which was significantly greater than that of more traditional methods.…”
Section: Introductionmentioning
confidence: 99%